Migration Pattern of Industrial Workers in Bekasi Regency - Sony Nugratama Hijrawadi; Adrian (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2019)
Bekasi Regency, which is located in the periphery cities of Jakarta and Bekasi, has experienced significant regional development. As an industrial area, Bekasi Regency is very attractive to prospective workers. The population problem that needs attention is the employment issue. As the population increases, the number of workers also increases. The purpose of this study is to geographically identify the area of origin of industrial labor in the Bekasi District which is the most dominant, to find out the characteristics of the industrial sector workforce based on their level of education and competence. This research used a quantitative descriptive method with a survey approach, and also conducted interviews with stakeholders, namely the local government of Bekasi Regency